PERTANGGUNGJAWABAN PIDANA PIHAK KREDITUR YANG MEMPEKERJAKAN DEBTCOLLECTOR DALAM PENYELESAIAN KREDIT MACET - Marcellina Denisanjaya; Yovita Arie Mangesti (Gapenas Publisher, 2022)
In this study, it will examine the criminal liability of creditors who employ debtcollectors in collecting bad debts. Card-Based Payment Instruments (APMK) regulated in PBI (Bank Indonesia Regulation) Number 14 of 2012, one example of a payment instrument that is often used by the public is the use of Credit Cards. With this payment instrument, it can pose several risks for the community, a problem that often occurs is delays or overdue in paying credit card bills. Until it finally causes credit bottlenecks in payments and also the nominal collection that is increasing due to late fees. The existence of credit congestion can cause other problems for the creditor and the debtor. In general, in the event of a bad debt, the creditor will use the services of a Debtcollector as a third party to collect debts. Debtcollector as a third party charged by the creditor (bank) in collecting debts to the debtor, but the power of attorney that has been given makes the debtcollector do various ways of collecting. There are some debt collection individuals who commit arbitrary acts or unlawful acts in collection. In this study, it uses normative juridical research methods with a statutory approach and a conceptual approach. The results of this study show that the form of criminal liability of creditors who employ debtcollectors can be in the form of imprisonment and/or fines of a certain amount of money for compensation to the aggrieved party. It has not been clearly regulated in the laws and regulations regarding the form of criminal liability of creditors in hiring debtcollectors who commit unlawful acts at the time of debt collection.